Drug errors before and after implementation of electronic prescribing on paediatric intensive care unit. (29th September 2015) - Neal, C; Naik, H; Fletcher, P; Inwald, D
Abstract : Aims: To identify the number and type of prescribing errors and dose omissions before and after implementation of electronic prescribing on Carevue (Phillips, UK), an ICU clinical information system, installed in our paediatric intensive care unit (PICU) in February 2009. Methods: Prospective audit of prescribing errors and missed doses for 96-h periods in three epochs—before implementation of Carevue (Epoch 1), one week after implementation of Carevue (Epoch 2) and 6 months after implementation of Carevue (Epoch 3). Prescribing errors were further classified as incomplete prescription, insufficient information, illegible prescription, prescribing error and other. The χ 2 was used to compare proportions. Results: Electronic prescribing on Carevue was associated with a significantly lower incidence of missed doses, likely due to electronic worklists and alerts for nursing staff. There was also a tendency towards a lower incidence of prescribing error, likely due to predefined standard orders for drugs and infusions commonly used on the PICU (figure 1). Incomplete prescription, insufficient information and illegible prescriptions as causes of prescribing error were not seen following implementation of Carevue. Conclusions: A clinical information system can significantly reduce the incidence of drug errors in PICU.